2013
DOI: 10.4253/wjge.v5.i5.270
|View full text |Cite
|
Sign up to set email alerts
|

Boerhaave’s syndrome during bowel preparation with polyethylene glycol in a patient with postpolypectomy bleeding

Abstract: Boerhaave's syndrome is spontaneous rupture of the esophagus, a rare condition with high mortality that occurs most often after forceful vomiting. Polyethylene glycol (PEG) solution is the most common preparation used for colonoscopy. Since large volumes have to be ingested, PEG may induce severe vomiting or retching. However, Boerhaave's syndrome has rarely been reported as a potential problem related to PEG solution. We report a case of spontaneous esophageal rupture due to violent vomiting during bowel prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Esophageal perforation is a life‐threatening condition, and mortality is high (11.9%) despite of surgical or medical treatment . Although there are several causes of esophageal perforation, only a few spontaneous esophageal perforation cases associated with PEG electrolyte solution for colonoscopy preparation have been reported . These previous reports and the present case suggested that esophageal rupture during colonoscopy preparation might be common in elderly adults (median 73, range 61–85).…”
mentioning
confidence: 47%
“…Esophageal perforation is a life‐threatening condition, and mortality is high (11.9%) despite of surgical or medical treatment . Although there are several causes of esophageal perforation, only a few spontaneous esophageal perforation cases associated with PEG electrolyte solution for colonoscopy preparation have been reported . These previous reports and the present case suggested that esophageal rupture during colonoscopy preparation might be common in elderly adults (median 73, range 61–85).…”
mentioning
confidence: 47%
“…We searched the literature in the databases Google Scholar, Medline, Web of Science, Embase, and Embase using keywords such as esophageal perforation, Boerhaave syndrome, bowel preparation, colonoscopy and complication. Few studies of esophageal rupture associated with colonoscopy and bowel preparation have been published (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Herein we have reported these studies' demographic features, symptoms, location of esophageal rupture, length of the laceration, diagnostic method, imaging findings, treatment and outcome in the following Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…This preparation requires ingesting a large amount and can lead to forceful vomiting. 9 In patients with Boerhaave syndrome, the most common presenting complaint is pain that is usually associated with the site of perforation and can occur in the neck, chest, or abdomen. 2 This may be associated with vomiting, painful swallowing, and voice change, or fever and physical examination may reveal the presence of tachycardia, tachypnea, and subcutaneous emphysema.…”
Section: Discussionmentioning
confidence: 99%